Direct collapse of exceptionally heavy black holes in the merger-driven scenario - Zwickel, Lorenz; Mayer, Lucio; Haemmerlé, Lionel; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2023)
We revisit the conditions present in supermassive discs (SMDs) formed by the merger of gas-rich, metal-enriched galaxies at redshift z ∼ 10. We find that SMDs naturally form hydrostatic cores which go through a rapidly accreting supermassive star phase, before directly collapsing into massive black holes via the general relativistic instability. The growth and collapse of the cores occurs within ∼5 × 105 yr from the formation of the SMD, producing bright electromagnetic, neutrino and gravitational wave transients with a typical duration of a few minutes and, respectively, a typical flux and a typical strain amplitude at Earth of ∼10−8 erg s−1 cm−2 and ∼4 × 10−21. We provide a simple fitting formula for the resulting black hole masses, which range from a few 106 to 108 M⊙ depending on the initial SMD configuration. Crucially, our analysis does not require any specific assumption on the thermal properties of the gas, nor on the angular momentum loss mechanisms within the SMD. Led by these findings, we argue that the merger-driven scenario provides a robust pathway for the rapid formation of supermassive black holes at z > 6. It provides an explanation for the origin of the brightest and oldest quasars without the need of a sustained growth phase from a much smaller seed. Its smoking gun signatures can be tested directly via multimessenger observations.
Online veröffentlicht am 9. November 2022
Gesehen am 08.02.2023